Reactive Mechanisms of LSCF Single-Phase and LSCF-CGO Composite Electrodes Operated in Anodic and Cathodic Polarisations. (20th August 2015) - Laurencin, J.; Hubert, M.; Couturier, K.; Bihan, T. Le; Cloetens, P.; Lefebvre-Joud, F.; Siebert, E.
Abstract: An in-house model for a MIEC or MIEC-CGO composite has been built in order to analyse the electrode operating mechanisms in anodic and cathodic polarisations (SOEC and SOFC modes). A special attention has been paid to take into account the electrode microstructure properties as well as the most likely processes occurring therein. The reactive pathway has been divided in a sequence of reaction steps with a first oxidoreduction at the gas/MIEC surface, and a second one in parallel at the electrode TPBs. The model has been calibrated on experimental data recorded at 800 °C on a LSCF electrode tested in a symmetrical test configuration. A good agreement was found between simulated and experimental polarisation curves by using the electrode microstructural properties extracted from a 3D reconstruction obtained by FIB-SEM tomography. Considering the LSCF single-phase electrode, simulation results have highlighted that the reactive pathway is governed by the oxygen exchange at the gas/MIEC surface in cathodic polarisation. The mechanism is found to remain unchanged at low anodic polarisation, whereas oxidation at TPBs becomes the predominant reactive pathway at higher polarisation. For the LSCF-CGO composite, simulations have shown that the reactive mechanism is governed by the charge transfer at TPBs whatever the electrode polarisation. Thanks to sensitivity analysis, the rate-limiting steps of the different reactive pathways are also discussed.